Implementasi Teknologi Pembukuan Digital Untuk Meningkatkan Efisiensi dan Akurasi Keuangan UMKM - Heny Triastuti Kurnia Ningsih; Lusi Elviani Rangkuti; Jalilah Ilmiha; Zufrizal Harahap; Dzakiyah Noor Hasibuan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This community service program aims to improve the efficiency and accuracy of financial records in MSMEs through the implementation of digital bookkeeping technology in Ladang Bambu Village, Medan Tuntungan District. The method included initial surveys, digital application training, intensive mentoring, and pre-test and post-test evaluations. The results indicated significant improvements, with 90% of participants able to digitally record transactions, 75% preparing simple financial statements, and 80% expressing confidence in continuing digital applications after the program. This program effectively addressed digital financial literacy gaps, improved reporting accuracy, and encouraged the use of technology in small business management. The main limitations were the short mentoring duration and the limited participant infrastructure